2009
DOI: 10.1002/anie.200904968
|View full text |Cite
|
Sign up to set email alerts
|

N2.3−: Filling a Gap in the N2n Series

Abstract: coordination chemistry · nitrogen · radical complexes · rare-earth metals · superoxide analoguesParallel to the elucidation of the heterogeneous catalytic reactions leading from adsorbed N 2 and H 2 to NH 3 under real or idealized conditions [1] and in addition to continued studies of enzymatic nitrogen fixation, [2] the primary products of N 2 reduction have received special attention as surface-or metalstabilized molecular ions. Thus, the one-electron addition to N 2 C À [3] and the stabilization of two-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…A recent synthetic-spectroscopic-computational study has described the first definitive examples of N 2 3− complexes, using dysprosium and yttrium (Figure 8). lxi These μ−η 2 :η 2 bridging dinitrogen ligands have N-N bond distances near 1.40 Å. The assignment of N 2 3− is supported by EPR studies on the Y compounds that show hyperfine splitting consistent with an N 2 -based radical, and DFT studies that reproduce the N-N bond distance and stretching frequency.…”
Section: Binding With "Three-electron Reduction" and "Four-electron Rmentioning
confidence: 83%
“…A recent synthetic-spectroscopic-computational study has described the first definitive examples of N 2 3− complexes, using dysprosium and yttrium (Figure 8). lxi These μ−η 2 :η 2 bridging dinitrogen ligands have N-N bond distances near 1.40 Å. The assignment of N 2 3− is supported by EPR studies on the Y compounds that show hyperfine splitting consistent with an N 2 -based radical, and DFT studies that reproduce the N-N bond distance and stretching frequency.…”
Section: Binding With "Three-electron Reduction" and "Four-electron Rmentioning
confidence: 83%
“…Odd-electron nitrogen oxidation states, instead, propose radical character and one-electron reduction mechanisms, but have not been observed in Chatt or Schrock cycles so far. However, this potential intermediacy of [N 2 ] ·– or [N 2 ] 3·– radical ions in metal complexes proved existence only very recently in dinuclear nickel, iron, and lanthanide complexes, respectively. , Thereby, [N 2 ] ·– were found to exhibit N–N bond lengths of about 1.13–1.18 Å and N–N stretching frequencies of 1740–1950 cm –1 , , ,, whereas the d NN in [N 2 ] 3·– ions was found to be at 1.39–1.41 Å with shifted N–N stretching energies of below 1000 cm –1 . To gain final evidence for the presence of such radical anions [N 2 ] ·– or [N 2 ] 3·– , electron spin resonance spectroscopy (ESR) revealed clearly visible signals in accordance with simulated spectra indicative of unpaired electrons and supporting the radical formulation of dinitrogen ligation. ,, …”
Section: Introductionmentioning
confidence: 99%
“…The (N 2 ) 3− radical was recently synthesized for the first time in complexes of dysprosium and yttrium, Schemes and . Although (N 2 ) 3− is isoelectronic with the well-known (O 2 ) − superoxide ion and dinitrogen reduction has been heavily studied, this oxidation level of reduced dinitrogen had remained elusive for decades. Density functional theory (DFT) studies on the complex of the closed shell Y 3+ ion indicated that the unpaired spin density in the (N 2 ) 3− radical was located in an orbital perpendicular to the metal orbitals and the isolation of this reactive species may be facilitated by the ionic nature of Dy 3+ and Y 3+ …”
Section: Introductionmentioning
confidence: 99%